PENGENDALIAN INTERN TERHADAP PENCAIRAN DANA BEASISWA DI DPPKAD (DINAS PENDAPATAN PENGELOLAAN KEUANGAN DAN ASET DAERAH) KEBUMEN - TRIANA, ENDANG SHYTA; ., Muntasripah (Politeknik Dharma Patria Kebumen, 2017)
Internal control is impotant to know what is going well or not, to determine the organization carried out approriately. Similiarly, with regard to the activities, especially  the disbursement of scholarship in DPPKAD Kebumen required the existence of an internal control. This study aims to determine the relationship between the internal control with the disbursement of scholarship in DPPKAD Kebumen . This research method using descriptive quantitative method. Data rigourus primary data  obtained through a questionaire to employees DPPKAD Kebumen relating to the disbursement of scholarships. The result showed that the the relationship between the disburement of scholarship have a very  strong relationship r=0,860 positive and significant at the 5% level. The coefificent of determination of r=0,765 showed that the disbursement of the scholarship is explained by the internal control amount to 76,5%, the remaining 23,5% is explained by other factors beyond the research